Sales Promotion Activities During Ganesh Festival: An Empirical Study with Reference to Pune City. - et. al., Dr. Preeti Sharma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In today's competitive market, sales promotion activities during the festival comes handy to the traders and corporate organizations to overcome their several sales/marketing issues or problems arise for the short term. In Indian market festivals period are extensively used for sales promotion activities. Through this study, an attempt has been made to understand the major objectives of sales promotion in Ganesh festival its benefits to the Ganesh festival organizers (Ganesh Mandals) and benefits to the traders/corporate organizations. This study also highlights the nature of the sales promotion mix offered by traders/corporate organizations, specifically during the festival period.